Enhancing quantum time transfer security: detecting intercept-resend attacks with energy-time entanglement - Quan, Runai; Hong, Huibo; Xiang, Xiao; Cao, Mingtao; Li, Xinghua; Li, Baihong; Dong, Ruifang; Liu, Tao; Zhang, Shougang (New journal of physics, 2024)
Quantum time transfer has emerged as a powerful technique, offering sub-picosecond precision and inherent security through the nonlocal temporal correlation property of energy-time entangled biphoton sources. In this paper, we demonstrate the inherent security advantage of quantum time transfer, and the utilization in detecting potential intercept-resend attacks. By investigating the impact of these attacks on the nonlocality identifier associated with nonlocal dispersion cancellation of energy-time entanglement, we establish a security threshold model for detecting intercept-resend attacks. Experimental verification on a 102 km fiber-optic link confirms that even a malicious delay as small as 25 ps can be identified. This investigation serves as a compelling illustration of secure two-way time transfer, safeguarding against intercept-resend attacks, and showcasing its potential applications in fields reliant on authentic time distribution between remote parties.